Dirāsah Tahlīliyah Fi Asālīb Ta‘Līmī Mahāratil Kalāmi Bi Kitāb Al Mumtāz Fil Hiwārāt Al-Yaumiyyah Lighairinātiqīna Bil Arabiyyah - Kudus, Ruhul; Muhammad Sofwan bin Harizan (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
This study aims to determine the method of teaching speaking skills in the Al-Mumtaz book in daily dialogue for non-Arabic speakers. The reason for choosing this topic is to provide an overview and information about the al-mumtāz textbook and some of its advantages. This book is structured only on one language skill, namely speaking. This research is a descriptive qualitative analytical research, and the method of data collection is the method of observation and documentation on the topic, and the method of data analysis through content analysis contained in Al-Mumtaz's book in the Daily Dialogue for Non- Arabic speakers. The advantages of this book and its analysis are the first: listening to the dialogue. Listening is the beginning of speaking skills. Second: understanding the contents of the dialogue to find out how far they understand the dialogue text Third: simulation and repetition which is an audio-lingual method Fourth: Language skills training such as word form training, communicative language training and meaning training Fifth: The vocabulary and phrases used are words and expressions that are widely used in everyday life so that students have sufficient vocabulary in different situations in their lives. Sixth: teaching vocabulary with pictures, and this method makes it easier for beginners to learn language, because they understand the meaning of pictures, not from translation or from mother language.